Pendampingan Pencegahan Tubercolusis (ACT Zero TB) dengan Skrining dan Rontgen Thorax di PMA Jamblangan Seyegan Sleman - Widianti, Emma (Journal of Humanity Dedication, 2024)
Zero TB Yogyakarta employs a comprehensive "find, treat, and prevent" approach in its efforts to eliminate TB in Yogyakarta. One of its activities in searching for TB cases in the community is active screening, also known as Active Case Finding (ACF). In this activity, participants undergo chest X-ray examinations, which are then read by a general practitioner. This Zero TB activity is conducted free of charge, with a quota of 120 people for implementation in Dukuh Jamblangan. The activity flow includes: (1) Actively finding TB cases (ACF), (2) Preventing TB, and (3) Treating TB. The target groups for the implementation of Zero TB are: (1) Residents in densely populated areas / areas far from health facilities, (2) Household contacts or close contacts of TB patients, (3) Healthcare workers, and (4) The elderly. The approach involves symptom screening and chest X-rays. The active role of community health centers (Puskesmas) such as outreach programs is an effective way to find more patients, despite being more costly. TB cases represent an iceberg phenomenon that requires joint efforts by all relevant stakeholders. The target is to reduce TB cases in Indonesia by 50 percent by 2025.